Hannah Arendt y la ética de la responsabilidade : una reflexión para el posconflicto colombiano - Martinez, Elkin Fabian (2020)
Our starting point has been the armed conflict and violence exerted between the Colombian Government and the FARC-EP, for almost half a century. At the base of our reflections is arendtian thought. Following Hannah Arendt, through the ethics of responsibility, reconciliation with the past and reorientation of political affairs is possible. This in the context of violence in the Colombian historical context between the FARC-EP and the State, in the so-called post-conflict. The ethics of responsibility in Arendt implies subjecting human actions to reflection and judgment in the field of plurality. The ethics of responsibility in Arendt implies subjecting human actions to reflection and judgment in the field of plurality. Thinking, thus, becomes the fundamental basis for human beings to adhere to reflection in active life. Our research is made up of four defining moments. In the first part, we delve into the Colombian historical context of the 20th century and the memory of this town. The starting point is the agrarian crises of the 20s. In the second part, we discuss Hannah Arendt's political thinking. The ability to think, to judge and to want [that drives an act], in relation to the action. In the third part, the human condition and care for the world are addressed. In the fourth part, we present some conclusions. Colombia, currently, is going through an important event: the hope of a better future, the opportunity to change its history through reconciliation with the past. There are several considerations that must be kept in mind, which are part of a reconciliation process: forgiveness, justice, truth, the reparation of victims, the reintegration of ex-guerrillas into public life, the ability to start again, etc. The responsibility to create a better future in Colombia depends on its ability to keep the life of the mind active.